Ambientes vulnerables. Aportes conceptuales y definiciones para el análisis de la vulnerabilidad de los sistemas ambientales - Freitas Scaraffuni, Gabriel (2024)
In recent decades, the changes wrought by human activities upon ecosystems have become increasingly apparent, leading to processes of environmental and social degradation. Certain analyses of this situation attribute a portion of the responsibility to epistemological and theoretical approaches, prompting the proposition of several alternative conceptual models.The concept of vulnerability has been employed to address environmental issues across various theoretical and methodological frameworks, resulting in a lack of consensus regarding its definition or models for application. While strides have been made in perspectives aiming to model territorial vulnerability in an integrated manner within a systems framework, limitations persist primarily in how the relationships among system components are assessed and represented.Beyond these constraints, the development of vulnerability models holds the potential to transcend linear intervention-impact paradigms and facilitate systemic analyses, rendering this field ripe for innovation. This article aims to propose a conceptual definition of vulnerability from the perspective of environmental systems, enabling the modeling of its spatial and temporal variability. This process will entail not only acknowledging the existence of multiple dimensions and their interrelations, but also integrating elements such as the emergent properties of the system, the specific definition of its functional degradation, and the recognition and consideration of stochastic processes inherent to open and dynamic systems.